Effectiveness of ketamine in the treatment of refractory and super-refractory status epilepticus in children - Wu, J (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2020)
Objective: To investigate the effectiveness of ketamine in the treatment of refractory status epilepticus (RSE) and super refractory status epilepticus (SRSE) in children. Methods: A retrospective study was conducted to collect and analyze the medical data of 18 children with RSE or SRSE who received ketamine in intensive care unit of Beijing Children's Hospital from January 2016 to December 2018. According to the different regimen of ketamine, all children were divided into the loading-maintenance group (7 cases) and the maintenance group (11 cases). According to the control of status epilepticus, the patients were divided into controlled group (11 cases) and non-responsive group (7 cases).Wilcoxon's rank sum test or Fisher's exact test were used to compare the effectiveness between groups. Results: There were 9 males and 9 females in the study group, aged 6.7 (4.5, 9.0) years. Seven cases had RSE and the remaining had SRSE. Four cases died during hospitalization. After the initiation of ketamine treatment, RSE and SRSE were controlled in 11 children. The duration of ketamine administration was 4 (2, 11) days. The dose was 2.2 (1.2, 5.3) mg/(kg·h) in all patients, and 2.4 (1.3, 6.0) mg/(kg·h), 2.0 (1.0, 4.0) mg/(kg · h) in the controlled and non-responsive group, respectively (Z=-0.272, P=0.791). The RSE or SRSE were terminated in all the 7 patients who received loading dose of ketamine, with the dose of 1.5 (0.3,1.6) mg/kg. In the 11 patients who only received maintenance treatment, 4 had the RSE and SRSE terminated, which showed a significantly lower effectiveness than in loading-maintenance group (7/7 vs. 4/11, P=0.01). Regarding the adverse reactions, saliva secretion increased in 8 children during the ketamine administration, otherwise unremarkable. Conclusion: Loading dose followed by maintenance of ketamine can control children's RSE and SRSE well, without significant adverse reactions